The Role Of Midwives In Achieving Complete Neonatal Visits In East Kasiruta District In 2026 - Kusrini Muhdar (CV. AFDIFAL MAJU BERKAH, 2026)
Neonatal mortality remains a significant public health challenge in Indonesia, accounting for the largest proportion of under-five deaths. Complete neonatal visits are essential to monitor newborn health, detect complications early, and provide appropriate health education to families. Midwives play a crucial role in ensuring the successful implementation of neonatal healthcare services at the community level.This study aimed to explore the role of midwives in the implementation of complete neonatal visits in East Kasiruta District in 2026.This study employed a qualitative observational design with a descriptive approach. Informants were selected using purposive sampling and consisted of mothers with infants aged 28 days to 11 months living in East Kasiruta District. Data were collected through structured questionnaires and interviews conducted from January 5 to January 10, 2026. The data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings revealed that all informants were aware of complete neonatal visits and generally understood their purpose in monitoring newborn health. Midwives were identified as the primary source of information regarding neonatal care, with four out of five informants obtaining information directly from village midwives. All informants reported receiving neonatal home visits during the first 28 days after birth; however, the frequency of visits varied from one to three visits. The study also identified additional factors influencing neonatal visit utilization, including husband support and local cultural traditions that discourage newborns from leaving the house before the age of 40 days. Midwives play a vital role in promoting and implementing complete neonatal visits in East Kasiruta District. However, improving neonatal healthcare coverage requires strengthening midwives’ outreach activities and increasing family and community awareness to overcome social and cultural barriers.